Inflammatory Biomarkers Comparison Between Benign Prostatic Hyperplasia Versus Prostate Cancer Patient in Secondary Hospitals, Bogor, Indonesia - Sulistyo, Alexander; Putra, Rosadi (Jurnal Locus Penelitian dan Pengabdian, 2026)
This research aimed to compare inflammatory biomarkers derived from complete blood counts—namely, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), systemic immune-inflammation index (SII), and systemic inflammation response index (SIRI)—between BPH and prostate cancer patients. A retrospective study was conducted on 257 patients from two secondary hospitals in Bogor, Indonesia, between January 2021 and June 2025. Subjects were diagnosed with either BPH (n = 212) or prostate cancer (n = 45). Preoperative complete blood counts were used to calculate NLR, PLR, MLR, SII, and SIRI. Group comparisons were performed using the Mann–Whitney U test, and multivariate analysis of variance (MANOVA) was conducted to assess overall biomarker profile differences. Binary logistic regression was applied to evaluate the predictive value of individual biomarkers. PLR was significantly higher in prostate cancer patients (p = 0.007), while other biomarkers did not show significant intergroup differences in univariate analysis. MANOVA revealed a statistically significant difference in overall inflammatory profiles (Pillai’s trace = 0.060, F(5, 251) = 3.208, p = 0.008). Logistic regression identified PLR (p < 0.001), SII (p = 0.035), and SIRI (p = 0.009) as independent predictors of prostate cancer. Inflammatory biomarkers—particularly PLR, SII, and SIRI—may serve as useful markers to differentiate prostate cancer from BPH and offer prognostic insight. These parameters are readily available from routine complete blood counts, making them valuable tools in clinical settings, especially in resource-limited areas. Further prospective studies are recommended to validate their utility and integration into standard diagnostic pathways.